Birthweight, postnatal growth and blood pressure in adolescents of low socioeconomic condition: a cohort study in Northeast Brazil - Marcelo de Santana Oliveira; Fabiana Cristina Lima da Silva Pastich Gonçalves; Pedro Israel Cabral de Lira; Sidrack Lucas Vila Nova Filho; Sophie Helena Eickmann; Marilia de Carvalho Lima (Elsevier, 2023)
Objective: To verify the influence of low birth weight and rapid postnatal weight gain and associated factors on blood pressure in adolescence in a population of low socioeconomic status, considering that injuries occur in the perinatal period can be predictors of future metabolic changes and are still poorly explored. Methods: A cohort study was carried out with 208 adolescents, 78 born with low weight and 130 born with appropriate weight. The infants were followed up during the first six postnatal months and reassessed at 8 and 18 years of age. The independent variables were birthweight and postnatal weight gain. Rapid postnatal weight gain was defined when above 0.67 z score. The co-variables were sex, maternal height and family income at birth, nutritional status at eight years old, socioeconomic conditions, nutritional status, fat mass index, and physical activity level at 18 years. The outcome variable was blood pressure at 18 years old. The bivariate and multivariable logistic regression analysis were realized and p < 0,05 was considered significant. Results: The proportion of adolescents with elevated blood pressure was 37.5%. The multivariable logistic regression analysis showed the variables independently associated with a higher chance of elevated blood pressure in adolescence were rapid postnatal weight gain (OR = 2.74; 95% CI 1.22-6.14; p = 0.014), male sex (OR = 4.15; 95% CI 1.66-10.38; p = 0.002) and being physically active (OR = 2.70; 95% CI 1.08-6.74; p = 0.034). Conclusions: The rapid postnatal weight gain was a predictor for elevated blood pressure in adolescence, independently of other factors.